Menebar kebaikan di bulan suci: aksi berbagi takjil dan buka bersama karang taruna dusun sangeng: - - fahira, firda umi (Maliki Interdisciplinary Journal, 2025)
The month of Ramadan is a significant moment in the social life of Indonesian society, especially as an opportunity to strengthen solidarity, deepen Islamic values, and foster positive interactions among community members. This article discusses a community service activity carried out by students from the KKM (Kuliah Kerja Mahasiswa) program of UIN Malang in Sangeng Kramat Hamlet, Bangil, during Ramadan 2025. The main focus of the activity was the distribution of takjil (light meals to break the fast) and the organization of communal iftar (breaking of the fast), conducted in close collaboration with the local youth organization, Karang Taruna. This study adopts a qualitative descriptive approach, employing observation, documentation, and active participation as data collection techniques. The results show that the takjil distribution and communal iftar not only provided direct benefits in the form of meals for fasting residents, but also created a social space that strengthened interpersonal relationships within the village community. The active participation of Karang Taruna youth reflects a spirit of mutual cooperation and the embodiment of religious values in tangible actions, while the involvement of KKM students served as a meaningful social learning experience and a realization of the Tri Dharma of Higher Education. Moreover, the activity helped foster a positive image of the youth organization and nurtured empathy among adolescents. Thus, initiatives like this have proven effective in building social networks, strengthening solidarity, and supporting the development of a caring and harmonious society. This form of community-based philanthropy demonstrates that the integration of spiritual and social values can generate sustainable positive impacts within society